2020
DOI: 10.1186/s12903-020-1062-4
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence in fixed implant prosthodontics: a retrospective study of 106 implant-supported monolithic zirconia crowns inserted in the posterior jaws of 90 patients

Abstract: Background: Artificial intelligence (AI) is a branch of computer science concerned with building smart software or machines capable of performing tasks that typically require human intelligence. We present a protocol for the use of AI to fabricate implant-supported monolithic zirconia crowns (MZCs) cemented on customized hybrid abutments. Methods: The study protocol consisted of: (1) intraoral scan of the implant position; (2) design of the individual abutment and temporary crown using computer-aided design (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 39 publications
0
46
0
1
Order By: Relevance
“…Biological complications were minimal. A recent in vivo study by Lerner et al [ 82 ] also reported very promising results for monolithic zirconia crowns fabricated on hybrid zirconia abutments following an IOS procedure. Success and survival rates after a mean of 3 years of follow-up were 91.3% and 99% respectively with a 1.9% biologic and 5.7% prosthetic incidence rate.…”
Section: Resultsmentioning
confidence: 99%
“…Biological complications were minimal. A recent in vivo study by Lerner et al [ 82 ] also reported very promising results for monolithic zirconia crowns fabricated on hybrid zirconia abutments following an IOS procedure. Success and survival rates after a mean of 3 years of follow-up were 91.3% and 99% respectively with a 1.9% biologic and 5.7% prosthetic incidence rate.…”
Section: Resultsmentioning
confidence: 99%
“…In fixed implant prosthodontics, in particular, the 3D position of the implant is captured through the use of a transfer device, the scanbody (SB), which is screwed on the fixture and scanned with an IOS [11]. This scan, together with that of the master model without SB, the antagonist and the bite are sent in standard tessellation language (STL) format to the dental laboratory, which uses CAD software to model the restorations (individual abutments, temporary, and then definitive restorations) [11]. Within the CAD software, the first and fundamental step performed by the dental technician is the replacement, on the master model, of the ME of the SB with the corresponding library file (LF) [11].…”
Section: Introductionmentioning
confidence: 99%
“…This scan, together with that of the master model without SB, the antagonist and the bite are sent in standard tessellation language (STL) format to the dental laboratory, which uses CAD software to model the restorations (individual abutments, temporary, and then definitive restorations) [11]. Within the CAD software, the first and fundamental step performed by the dental technician is the replacement, on the master model, of the ME of the SB with the corresponding library file (LF) [11]. This LF is aligned with all the components (titanium bonding bases with different shape and height) necessary for modelling the prosthetic restorations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations